Neonatal risk factors for respiratory morbidity during the first year of life among premature infants - Mello, Rosane Reis de; Dutra, Maria Virgínia Peixoto; Ramos, José Roberto; Daltro, Pedro; Boechat, Márcia; Lopes, José Maria de Andrade (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: There have been dramatic increases in very low birth weight infant survival. However, respiratory morbidity remains problematic. The aim here was to verify associa- tions between pulmonary mechanics, pulmonary structural abnormalities and respiratory morbidity during the first year of life. DESIGN AND SETTING: Prospective cohort study at Instituto Fernandes Figueira, Fundação Oswaldo Cruz, Rio de Janeiro. METHODS: Premature infants with birth weight < 1500 g were studied. Lung function tests and high-resolution chest tomography were per- formed before discharge. During the first year, infants were assessed for respiratory morbidity (obstructive airways, pneumonia or hospitaliza- tion). Neonatal lung tests and chest tomography and covariables potentially associated with re- spiratory morbidity were independently assessed using relative risk (RR). RR was subsequently adjusted via logistic regression. RESULTS: Ninety-seven newborn infants (mean birth weight: 1113g; mean gestational age: 28 weeks) were assessed. Lung compliance and lung resistance were abnormal in 40% and 59%. Tomography abnormalities were found in 72%; respiratory morbidity in 53%. Bivariate analysis showed respiratory morbidity associated with: mechanical ventilation, prolonged oxygen use (beyond 28 days), oxygen use at 36 weeks, respiratory distress syndrome, neonatal pneu- monia and patent ductus arteriosus. Multivari- ate analysis gave RR 2.7 (confidence interval: 0.7-10.0) for simultaneous lung compliance and chest tomography abnormalities. Adjusted RR for neonatal pneumonia and mechanical ventilation were greater. CONCLUSIONS: Upon discharge, there were high rates of lung mechanism and tomography abnormalities. More than 50% presented respi- ratory morbidity during the first year. Neonatal pneumonia and mechanical ventilation use were statistically significant risk factors.